Enhancing female status by improving nutrition: The role of corporate social responsibility in Nigeria's oil region - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2022)
The purpose of this paper is to critically examine the multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on improving female status by improving nutrition in the Niger Delta region of Nigeria. This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially cross-sectional, describing and interpreting the current situation. A total of 768 women respondents were sampled across the rural areas of the Niger Delta region. The results from the use of a combine propensity score matching and logit model indicate that GMoU model has made significant impact in the key areas of assessment - gender-sensitive nutrition education, food security at household level, reduction on food taboos and female access to education. This suggests that CSR interventions targeting to improve the nutrition status of girls and adolescents will help to ensure that female's status improves throughout the life circle in the region. This implies that MOCs' investment in the nutrition of female is an important short-term barometer in assessing expected returns to improving household nutrition and overall human development capacity for sub-Saharan Africa. This research contributes to the inequality debate in the women's nutrition and inclusive growth literature from the CSR perspective. It concludes that business has an obligation to help in solving problems of public concern.
Keywords: 330; Female status; female nutrition; corporate social responsibility; multinational oil companies; sub-Saharan Africa